(untitled) (Scientific journal of the Fergana State University, 2023)
The article explores the beginning of a new era in the political, economic and cultural-humanitarian cooperation of the Uzbek and Turkish peoples, the General History, fraternal relations that created it, as well as the development of the national traditions of the two peoples